Static inflation and deflation pressure-volume curves from excised lungs of marine mammals - Fahlman, Andreas; Loring, Stephen H.; Ferrigno, Massimo; Moore, Colby; Early, Greg; Niemeyer, Misty; Lentell, Betty; Wenzel, Frederic; Joy, Ruth; Moore, Michael J. (Journal of Experimental Biology, 2011)
Excised lungs from eight marine mammal species [harp seal ( Pagophilus groenlandicus ), harbor seal ( Phoca vitulina ), gray seal ( Halichoerus grypus h), Atlantic white-sided dolphin ( Lagenorhynchus acutus ), common dolphin ( Delphinus delphis ), Risso's dolphin ( Grampus griseus ), long-finned pilot whale ( Globicephala melas ) and harbor porpoise ( Phocoena phocoena )] were used to determine the minimum air volume of the relaxed lung (MAV, N =15), the elastic properties (pressure–volume curves, N =24) of the respiratory system and the total lung capacity (TLC). Our data indicate that mass-specific TLC (sTLC, l kg–1) does not differ between species or groups (odontocete vs phocid) and agree with that estimated (TLC est ) from body mass ( M b ) by applying the equation: TLC est =0.135 M b 0.92. Measured MAV was on average 7% of TLC, with a range from 0 to 16%. The pressure–volume curves were similar among species on inflation but diverged during deflation in phocids in comparison with odontocetes. These differences provide a structural basis for observed species differences in the depth at which lungs collapse and gas exchange ceases.